Nanotecnología aplicada a la medicina - Pájaro Castro, Nerlis (Universidad de San Buenaventura - Cali, 2017)
Nanotechnology involves the creation, manipulation and use of materials at the nanometer scale (10-9 m). This field is enabling new advances in science, with applications in fields such as chemistry, biology, physics, engineering, and particularly in medicine. The latter called nanomedicine, has generated advances in monitoring, tissue repair, diagnosis, treatment and prevention of diseases, using tools such as nanosensors, nanocrystals, nanoparticles, nanotubes, and in the near future, nanorobots, capable of penetrating the human body to repair it. Nanotechnology is in a growth stage, capturing the interest of companies, governments and investors to develop products useful in several fields, especially in medicine.